Azimuthal Seismic Anisotropy of 70‐Ma Pacific‐Plate Upper Mantle. Issue 2 (16th February 2019) - Mark, H. F.; Lizarralde, D.; Collins, J. A.; Miller, N. C.; Hirth, G.; Gaherty, J. B.; Evans, R. L.
Abstract: Plate formation and evolution processes are predicted to generate upper mantle seismic anisotropy and negative vertical velocity gradients in oceanic lithosphere. However, predictions for upper mantle seismic velocity structure do not fully agree with the results of seismic experiments. The strength of anisotropy observed in the upper mantle varies widely. Further, many refraction studies observe a fast direction of anisotropy rotated several degrees with respect to the paleospreading direction, suggesting that upper mantle anisotropy records processes other than 2‐D corner flow and plate‐driven shear near mid‐ocean ridges. We measure 6.0 ± 0.3% anisotropy at the Moho in 70‐Ma lithosphere in the central Pacific with a fast direction parallel to paleospreading, consistent with mineral alignment by 2‐D mantle flow near a mid‐ocean ridge. We also find an increase in the strength of anisotropy with depth, with vertical velocity gradients estimated at 0.02 km/s/km in the fast direction and 0 km/s/km in the slow direction. The increase in anisotropy with depth can be explained by mechanisms for producing anisotropy other than intrinsic effects from mineral fabric, such as aligned cracks or other structures. This measurement of seismic anisotropy and gradients reflects the effects of both plate formation and evolution processes on seismic velocity structure in mature oceanic lithosphere, and can serve as a reference for future studies to investigate the processes involved in lithospheric formation and evolution. Key Points: We measure 6.0 ± 0.3% anisotropy at the Moho in 70‐Ma oceanic lithosphere, increasing to 7.7% at 7 km below the Moho The increase in anisotropy with depth suggests the presence of an extrinsic source of anisotropy, such as oriented cracks The fast direction is along 83 ± 1°N, parallel to paleospreading